Pengaruh Flash Sale dan Live Streaming terhadap Pembelian Impulsif melalui Rasa Takut Ketinggalan (FOMO) di TikTok Shop - Moch Ilham Firmansyah; Ika Diyah Candra Arifah; Ratih Amelia; Nadia Nur Thahirrah (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the impact of Flash Sale and Live Streaming on Impulsive Buying with the fear of missing out (FOMO) factor positioned as a mediating variable related to TikTok Shop consumers. My study uses a quantitative approach using the causal associative method. Data were collected through an online questionnaire to 100 TikTok Shop user respondents, and then analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4 for analyze relatedness between Flash Sale, Live Streaming, FOMO, and Impulsive Buying . The results of the study show that Flash Sale has a positive and significant effect on FOMO, Live Streaming has a positive and significant effect on FOMO, Flash Sale has a positive and significant effect on Impulsive Buying, Live Streaming has a positive and significant effect on Impulsive Buying, and FOMO has a positive and significant effect on Impulsive Buying. FOMO is also proven to mediate the influence of Flash Sale and Live Streaming on Impulsive Buying. These findings indicate that promotional stimuli and digital shopping interactions can encourage impulsive buying through the fear of missing out on offers.